Technology of quality assessment of critical software systems based on ontological modeling - Raichev, I.E. (Problems of Informatization and Management, 2025)
The article investigates the problem of identifying and analyzing the requirements for program systems of critical purpose. For a variety of mission-critical system classes, the task of developing methods for verifying these systems for compliance with the specified requirements within the subject domain and analyzing risks and hazards throughout their life cycle is relevant. Compliance assessment is typically performed by evaluating the overall quality level of flight control software components during the testing phase. To comprehensively analyze the compliance of system attributes with the specified requirements, it is necessary to examine and structure a significant number of objects and functions. To address the problem of systematization within the subject domain, it is proposed to build a formal conceptual model of the system, based on which a set of objects, basic functions, and a quality model to assess the quality level of the system can be technologically formed. The problem of improving the safety of the operation of objects controlled with automated flight control systems is still relevant. One way to achieve this goal is to ensure the quality and reliable functioning of the flight control systems, which is especially important during the operation of the tolerance control subsystem, which should ensure the complete implementation of control algorithms established for each type of aircraft. In the case of incorrect piloting and operation of units and equipment, there are risks to allow further flights to an unprepared crew or board of the aircraft, which has defects of equipment, which can cause an aviation incident that directly affects the safety of people’s lives, as well as the integrity of the aircraft. The way to solving the problem is the effective use of the ontological model of components of the flight control software systems to create a system of knowledge of the subject area of automated flight control systems. The article analyzes recent research and publications, which shows the effectiveness of using ontology to implement the decision-making process in the context of problematic ambiguity situations. For flight control systems, ontological research apparatus can be effectively used, as the main task of the software is to decide on the receipt of the control object during the flight in the state "within the admission" (regular regime) or "beyond tolerance". The developed ontological model determines the composition, classification, structure and interconnection of requirements and risks and can forms a technological procedure for creating a quality model of critical PS and the concept of evaluating its characteristics and attributes. Ontological studies and created ontology directly indicate the quality properties that need to be included in the quality models and provide tools for constructing quality models: 1) Target quality model for the developer of the flight control system. 2) Quality in use model for the aircraft operator. The conducted researches include: 1) Execution of ontological analysis of the subject area of application. 2) Creation of ontology of flight control software, which systematizes and structures knowledge of the concepts and objects of the subject area. 3) Formation of functions of interpretation of ontology, as well as specifications of criteria and restrictions for decision-making problems in critical systems. 4) Formation of specifications of requirements for reliability and safety of flight control systems based on the detection and generalization of components of risk analysis and dangers of functioning of critical software systems. 5)Construction of the target quality model and quality in use model for a given subject area and creation of methodology for evaluating the integral level of quality of flight control software. The conclusions state that an ontological model and quality models can be used in the life cycle of different classes of control systems (including for certification), since any PS of control are characterized by the presence of a control object, which is controlled by a set of parameters measured by parametric information. The results, obtained in the article, can be apply by developers to create their own quality management system of any critical PS in different subject areas of application. Further research is proposed to conduct a deeper analysis of the technology of integral assessment of the quality of the PS, especially in terms of normalization of metrics of quality attributes in order to unify them.